The intergenerational transmission of higher education: Evidence from the 1973 coup in Chile - María Angélica Bautista; Felipe González; Luis R. Martínez; Pablo Mu\~noz; Mounu Prem (Queen Mary University of London, School of Economics and Finance, 2023)
We estimate the transmission of higher education across generations using the arrival of the Pinochet dictatorship to Chile in 1973 as natural experiment. Pinochet promoted a large contraction in the number of seats available for new students across all universities. Using census data, we find that parents who reached college age shortly after 1973 experienced a sharp decline in college enrollment. Decades after democratization, we observe that their children are also less likely to enroll in higher education. The results imply large and persistent downstream effects of educational policies over more than half a century.
Keywords: 330; Studies; educational attainment; higher education policy; intergenerational mobility; Chile; Studium; Bildungsabschluss; Hochschulpolitik; Intergenerationenmobilität; Chile